Parent–Child Relationship, Parenting Practices and Family Wellbeing in China - Feng, Zhiyang (2022)
The goal of the present thesis was to investigate associations between parent–child relationship, parenting practices and family wellbeing (parent and child) in China. The current thesis investigated the quality of parent–child relationship, parenting practices, child and parental wellbeing with a focus on the importance of parent–child relationship as a key variable. In order to accomplish the goal, quantitative data was collected from a Chinese parenting group (The Tulip System). The target group was parents who have 4–12 year–old children (n = 104, M = 8.40, SD = 3.50). Data on parent–child relationship, parenting practices, and family wellbeing (parental mental states and child behaviours) was collected by parent questionnaires. The results of the thesis suggested a key role of parent–child relationship, as it was related to parenting practices and family wellbeing outcomes, such as less child behaviour problems under parent–child closeness, more parental depression, anxiety and stress because of parent–child conflict. The results of the study indicated that parent–child relationship may play mediating role between parenting practices and child wellbeing. The current thesis highlighted the limited effects of parent–child relationship on parental wellbeing, in particular, parent–child closeness did not improve parental wellbeing. Additionally, the mediating role of parent–child relationship between parenting practices and parental wellbeing was not verified. The present thesis sets ground for further studies aiming at enhancing parent–child relationship by improving parenting practices, which would benefit both child and parental wellbeing.